A stepwise approach to conduit puncture for electrophysiological procedures in patients with Fontan circulation. Issue 6 (14th June 2017) - Uhm, Jae-Sun; Kim, Nam Kyun; Yu, Hee Tae; Yang, Pil-Sung; Kim, Jung Ok; Kim, Tae-Hoon; Song, Mi Kyoung; Lee, Sang-Yun; Joung, Boyoung; Pak, Hui-Nam; Choi, Jae Young; Jung, Jo Won; et al.
Abstract: Aims: In patients with Fontan circulation, the conduit may be punctured for electrophysiological procedures. We evaluated the feasibility and safety of a stepwise approach to conduit puncture in adults who have undergone Fontan operation. Methods and results: We included 13 consecutive patients with lateral tunnel or extracardiac conduit Fontan circulation [median age (interquartile range), 24.0 (16.0–25.0) years; seven men] who had undergone electrophysiological procedures. We performed a stepwise approach to conduit puncture: 1st, Brockenbrough needle; 2nd, Brockenbrough needle with snare; 3rd, extra-steep Brockenbrough needle with/without snare; 4th radiofrequency transseptal needle with/without snare; 5th, wiring through the puncture; 6th, conduit dilation with angioplasty balloon; 7th, non-compliant or cutting balloon; and 8th, Inoue dilator. In 12 patients, conduit puncture was successful. In two, one, and two patients with a lateral tunnel made of the pericardium or right atrial wall, conduit puncture was performed by steps 1st, 2nd, and 4th, respectively. In one, three, two, and one patient with the Goretex lateral tunnel or extracardiac conduit, conduit puncture was performed by steps 1st, 6th, 7th, and 8th, respectively. Puncture time was significantly longer in patients with Goretex conduits than with pericardial conduits [62.0 (50.0–120.0) and 11.5 (10.0–14.8) min, respectively; P < 0.001]. A snare was necessary in patients with angles ≤ 35° between the conduit wall and vertical line. Conclusion: A stepwise conduit puncture approach is feasible and safe in patients with lateral tunnel and extracardiac conduit Fontan circulation. Goretex conduit puncture was more difficult than pericardial conduit puncture.